REPRESENTASI PEREMPUAN DALAM VIDEO KLIP GIRLBAND KOREA (ANALISIS SEMIOTIKA VIDEO KLIP DALLA DALLA DARI GIRLBAND ITZY) - Salma Zuhaira (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Feminism is a social movement that demands justice and equal rights of women with men. Gender equality is still a matter of debate. One of them is in South Korea. Women who support feminism are considered to hate, do not need, and will feel their position is higher than men. This demand for equality covers the fields of economy, politics, social, lifestyle, culture and so on. This research was conducted with the aim of knowing how the representation of women displayed by Korean Girlband Itzy in their video clip entitled Dalla Dalla. Dalla-Dalla's video clip with the theme of women's freedom depicts the life movements of women who want freedom from the criticisms of others who consider them weak and discriminate. This video clip also shows them different from the others. Although in this video clip it is not clearly stated the relevance of feminism in it. Therefore, in order to get a detailed description of the issue of feminism and women in the video clip, the researcher uses John Fiske's semiotic theory with the main theory, namely The Codes of Television, to see that behind the video clips there are connotative and denotative representations. According to John Fiske's Semiotics, there are 3 levels, namely the level of reality, representation and ideology. So it is hoped that the representation of women in this video clip is clearly described. The results of the study show the meaning of signs at the level of reality, and representations indicate freedom, self-confidence, and personal existence. At the ideological level, it shows the existence of postmodern feminism. So at the level of signs and symbols related to the representation of post-modern feminism, namely creating new discourses or messages that are meaningful and provide positive energy to other women, so that they dare to fight oppression and discrimination. The song lyrics and narrative code in the video clip show several scenes that lead to on postmodern feminist symbols.